An efficient, high‐throughput method for the simultaneous exposure of drought stress and bacterial infection in plants - Choudhary, Aanchal (Appl Plant Sci, 2020)
PREMISE: We developed a systematic protocol for the easy, high‐throughput, qualitative, and quantitative assessment of the patho‐morphological, physiological, and molecular responses of Arabidopsis thaliana plants simultaneously subjected to drought and bacterial infection. This approach will assist studies elucidating plant adaptation strategies to combat combined stresses. METHODS AND RESULTS: Plants were grown in small screw‐capped containers, individual pots, or pot strips. Watering was withheld from 30‐day‐old plants, which were subsequently infected with Pseudomonas syringae pv. tomato DC3000 using a dip inoculation. The natural development of both drought and bacterial infection was successfully and rapidly replicated in large numbers of plants, which is difficult to achieve with existing protocols. CONCLUSIONS: Our protocol offers a simple, low‐cost, high‐throughput strategy for the rapid and easy bacterial infection of large numbers of plants. It can be used in large‐scale mutant and ecotype screenings under combined stresses and for other foliar pathogens in different plant species.